Sporotrichosis: An emergent disease - Zeppone Carlos, Iracilda [UNESP]; Batista-Duharte, Alexander (Springer Nature, 2015)
In recent decades, the frequency of invasive fungal infections has increased steadily, resulting in considerable morbidity and mortality. The increasing number of fungal infections has significantly contributed to health-related costs. The outcome of an infection with a human-pathogenic fungus often depends on the immune status of the host organism. Patients with a weakened immune system are at high risk of developing a serious fungal infection. On the other hand, increased prescribing of antifungals has led to the emergence of resistant fungi, resulting in treatment challenges. Sporothrix complex is an environmental pathogenic fungus found worldwide in soil, plants, and decaying vegetables. It is the etiological agent of sporotrichosis in humans and several domestic animals. Sporotrichosis was a neglected disease; however, it is now considered an emergent disease and is causing concern for the health authorities of several tropical and subtropical countries such as Brazil, Mexico, and Peru. Over the past decade, the incidence of sporotrichosis has been on the rise, and currently different fungal genotypes may be closely associated with the virulence of this fungus. Some leisure and occupational activities, such as agriculture and floriculture, have been associated with transmission of the disease, but today it is considered an important zoonosis, particularly in Brazil. This chapter also presents cases of sporotrichosis reported worldwide to show a picture of this disease.
Keywords: Emergent disease; Outbreaks; Sporothrix schenckii; Sporotrichosis